A modern look at a medieval bilayer metal leaf: nanotomography of Zwischgold. Issue 40 (10th October 2022) - Wu, Qing; Soppa, Karolina; Müller, Elisabeth; Müller, Julian; Odstrcil, Michal; Tsai, Esther Hsiao Rho; Späth, Andreas; Holler, Mirko; Guizar-Sicairos, Manuel; Butz, Benjamin; Fink, Rainer H.; Watts, Benjamin
Abstract : Many European sculptures and altarpieces from the Middle Ages were decorated with Zwischgold, a bilayer metal leaf with an ultra-thin gold face backed by silver. Abstract : Many European sculptures and altarpieces from the Middle Ages were decorated with Zwischgold, a bilayer metal leaf with an ultra-thin gold face backed by silver. Zwischgold corrodes quickly when exposed to air, causing the surface of the artefact to darken and lose gloss. The conservation of such Zwischgold applied artefacts has been an obstinate problem. We have acquired quantitative, 3D nanoscale images of Zwischgold samples from 15 th century artefacts and modern materials using ptychographic X-ray computed tomography (PXCT), a recently developed coherent diffractive imaging technique, to investigate the leaf structure and chemical state of Zwischgold. The measurements clearly demonstrate decreasing density (increasing porosity) of the leaf materials and their corrosion products, as well as delamination of the leaves from their substrate. Each of these effects speak to typically observed issues in the conservation of such Zwischgold applied artefacts. Further, a rare variant of Zwischgold that contains extremely thin multiple gold layers and an overlapping phenomenon of Zwischgold with other metal leaves are observed through PXCT. As supportive data, scanning electron microscopy (SEM) and scanning transmission electron microscopy (STEM) coupled with energy dispersive X-ray analysis (EDX) were performed on the medieval samples.